Implementation of the principles and norms of international law in „the Law of Georgia on the Occupied Territories“ - Gvaramia, Vepkhvia (COLLECTION OF SCIENTIFIC WORKS OF SOKHUMI UNIVERSITY, 2023)
The publication assesses the formal character of the peace agreements of the occupied territories of Georgia in the 1990s, which blocked the use of international legal mechanisms for quickresponse to theconflict. This process was called „ethnic conflict“ by Interested party. Non-fulfillment of treaties by the Russian Federation, misinterpretations of the principles of international law and actions taken on this basis increased the conflict, which led to the 2008 war, again agreements, their violation and recognition of the occupied territories. The publication highlights the expediency of the adoption of „the Lawof Georgia on the Occupied Territories“, It should not be canceled, since the law has given the conflict an international character, which allows Georgia to use the mechanisms of international law effectively in time. Dogmatic material is analyzed, which prohibits the appropriation of the territory by occupation or other method of coercion, despite of the effective control of the occupied territories. Underscores the importance of the decision of the European Court of Human Rights in the case of Georgia v. Russian Federation in respect of human rights violations in the occupied territories.This document, the principles of international law, „the Lawof Georgia on the Occupied Territories“ and the opinions of scholars,together, allow us to conclude that complexly presented circumstances give the Georgian legislature and executive authoritiesopportunity to take effective action to apply international legal mechanisms.Quick response is a guarantee of territorial integrity in Georgia.